(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The uppermost Bajocian to lowermost Bathonian ammonoid succession has been studied in the Bas Auran area in view of choosing one of its sections as the Global Stratotype Section and Point (G.S.S.P.) of the Bathonian Stage. The Bas Auran ammonite assemblages display exceptional values of record quality. The stratigraphic distribution of 629 specimens referred to 63 species and 35 genera, collected during the last forty years from three sections (Ravin du Bès, Ravin d’Auran, Ravin des Robines), is plotted and analyzed, bed by bed. Over 85 stratigraphic levels, through 9 m in thickness, have been studied at the top of the "Marno-calcaires à Cancellophycus" formation, ranging from the latest Bajocian (Parkinsoni Zone, Bomfordi Subzone) to the earliest Bathonian (Zigzag Zone, Convergens Subzone) and the base of the Macrescens Subzone. Ammonoid assemblages are composed of Northwest European and Mediterranean elements, associated with Sub-Mediterranean ones, allowing chronocorrelation between the Northwest European Convergens Subzone and the Sub-Mediterranean Parvum Subzone. The basal boundary of the Zigzag Zone and of the Bathonian Stage is placed at the base of Sturani’s bed 23 in the Ravin du Bès section and is identified by the first occurrence of Gonolkites convergens, and coincides with the lowest occurrence of Morphoceras parvum. Features of the ammonoid succession indicate relatively homogeneous and good record quality, gradual biostratigraphic change and high degree of taxonomic similarity between the Bomfordi and Convergens subzones. Palaeontological criteria also indicate relatively high values of palaeontological and stratigraphic completeness at the base of levels RB070-RB071 (= level 23 in Sturani 1967) which corresponds to the Bajocian/Bathonian boundary. The Ravin du Bès Section, with forty-six successive ammonoid fossil-assemblages of the Convergens Subzone belonging to three biohorizons through five metres of thickness, shows maximum values of biostratigraphic and biochronostratigraphic completeness, being one of the most complete in the world. Therefore, the Ravin du Bès Section should be chosen as the Global Stratotype Section and Point for the base of the Bathonian Stage. Two biostratigraphic logs summarize the ammonite content from the uppermost Bomfordi to basal Macrescens subzones. Three plates illustrate the most characteristic ammonoid taxa at the Bajocian-Bathonian passage in the Bas Auran succession.